A PERCEPÇÃO DO AMBIENTE FAMILIAR E A QUALIDADE DE VIDA DE ADOLESCENTES EM CUMPRIMENTO DE MEDIDA SOCIOEDUCATIVA. - TAVARES, ANA LUIZA (2018)
Data on the growth of adolescents in conflict with the law show that although they describe characteristics of a profile of these adolescents, few studies focus on the experiences of these adolescents and their families on the perception of the place they occupy and which reflections on the situation of being in conflict with the law. To think about interventions, it is necessary to understand the perception of these adolescents about their condition of existence and what negative and positive influences for the moment in which they live. The present research had as proposal to study the perception of adolescents in compliance with MSEMA, based on how they perceive the environment and family relations and the perception of quality of life in the MSEMA compliance period, among the quality of life issues, especially those related to the link with the social environment. The study group consisted of 22 adolescents with 18 years of age. The instruments were: Family Environment Scale (FES), WHOQOL-100 and socio-demographic questionnaire. The sample presented as a result factors such as low educational level or disagreement with age-appropriate schooling, use of substances such as alcohol, cigarettes and marijuana, have low socioeconomic income that ends up being related to low scores in the FES subscales as Guidance for Culture and Recreation and Recreational Activities and also with the low appreciation of the Environment Domain in the WHOQOL-100, the sample also presents low score in the FES in the sub-scale of Organization, Assertiveness and Control indicating family formation with hierarchy and roles not clearly defined, inflexibility and mismatch to deal with internal changes and external interferences in the family group. It is understood the need to expand the work with a larger number of participants and to insert the participation of the families, thus enabling a deeper analysis of the adolescents 'and their families' perceptions regarding their relationships and relationships with the environment and especially with the public policies that must be involved in the socio-educational work providing the social and health promotion of these adolescents with a new perspective of being a citizen and no longer be in conflict with the law.